Molecular neuroendocrinology : from genome to physiology - Murphy, David, 1957-; Gainer, Harold (Chichester, West Sussex ; Hoboken, NJ : Wiley Blackwell, 2016)
"Discusses the mechanisms that enhance peptide and protein diversity beyond what is encoded in the genome through post-translational modification"--
7.3 Techniques used to study the rate of peptide biosynthesis7.4 Dynamics of intracellular proteins and peptides; 7.5 Perspectives; References; CHAPTER 8: Neuropeptidomics; 8.1 Neuropeptides -- one gene, multiple products; 8.2 Mining the neuropeptidome 21st-century style using mass spectrometry-based 'omics approaches; 8.3 What do all these peptides do? Follow-up functional studies; 8.4 Perspectives; Acknowledgments; References; Further reading; CHAPTER 9: Posttranslational Processing of Secretory Proteins; 9.1 Posttranslational modifications of secretory proteins
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Neuroendocrinology -- Molecular apects; SCIENCE / Life Sciences / Neuroscience; Electronic books; Electronic books